Seeking similarity: how immigrants and natives manage at the labor market - Olof Åslund; Lena Hensvik; Oskar Nordström Skans (Institute for the Study of Labor (IZA), 2009)
We show that immigrant managers are substantially more likely to hire immigrants than are native managers. The finding holds when comparing establishments in the same 5-digit industry and location, when comparing different establishments within the same firm, when analyzing establishments that change management over time, and when accounting for within-establishment trends in recruitment patterns. The effects are largest for small and owner-managed establishments in the for-profit sector. Separations are more frequent when workers and managers have dissimilar origin, but only before workers become protected by EPL. We also find that native managers are unbiased in their recruitments of former co-workers, suggesting that information deficiencies are important. We find no effects on entry wages. Our findings suggest that a low frequency of immigrant managers may contribute to the observed disadvantages of immigrant workers.
Keywords: J15; J21; J62; M51; 330; Minority workers; labor mobility; workplace segregation; Arbeitsnachfrage; Migranten; Bevölkerung; Führungskräfte; Ethnische Gruppe; Personalbeschaffung; Arbeitsmarktdiskriminierung; Schweden